Avaliação das reações adversas e do desfecho clínico em pacientes tratados para tuberculose multirresistente atendidos no Hospital Universitário João de Barros Barreto - FANZLAU, Christe Ellen Batista (2019)
Objective: To evaluate the impact of adverse reactions on the clinical outcome in patients treated for multiresistant tuberculosis treated at the University Hospital João de Barros Barreto. Methodology: An observational, retrospective cohort study of cases of multidrug-resistant tuberculosis registered on SITE-TB, which underwent treatment from January 2010 to December 2015. Results: A total of 152 patients who presented with a mean age of 40, 2 years old, predominantly male (65.1%), brown breed (69.1%). The majority of the patients had less than seven years of study (62.4%) and was concentrated in the metropolitan region of Belém (73.7%), with a predominance of the unemployed (25%). Significant share presented secondary resistance (88.2%). Regarding drug use, alcohol use was more frequent (20.4%), followed by illicit drugs (16.5%) and tobacco (5.3%). The presence of comorbidities was low (27.6%), and Diabetes Mellitus was the most common (23%). Half of the patients in the study had adverse reactions and the most significant were arthralgia (31.6%), epigastric pain (15.1%) and peripheral neuropathy (5.3%). The favorable clinical outcome was predominant in 77% of the cases. The male gender (26.3%) presented more unfavorable outcome when compared to the female (17%). Among the occupations, the unemployed had the highest percentage of unfavorable outcome (39.5%). Among the patients presenting with comorbidity, the majority presented a favorable outcome (88.1%). As well as those with adverse effects also had a more favorable outcome (79.0%), however this data did not reach statistical significance (p = 0.563). The users of illicit drugs and tobacco showed a higher frequency of unfavorable outcomes (56.0% and 62.5%, respectively). In contrast, among alcohol users, the majority had a favorable outcome (54.8%). Conclusion: Multidrug-resistant tuberculosis remains an important public health problem, with high frequency, especially among the economically active population. Certain situations influence the clinical outcome of the treatment contributing to the dissemination of multidrug-resistant strains.